Answer:
H
Step-by-step explanation:
I'm legit smart bro quit playing
A. 4x - 3 = 2x + 7
4x - 2x = 7 + 3
2x = 10
x = 5
B. 2x + 6 = 7x - 14
2x - 7x = - 14 - 6
-5x = -20
x = 4
C. 2( x + 3) = x - 4
2x + 6 = x - 4
2x - x = -4 - 6
x = -10
D.4 ( 5x - 2) = 2( 9x + 3)
20x - 8 = 18x + 6
20x - 18x = 6 + 8
2x = 14
x = 7
E.4x - 1/2 = x - 7
4x - x = -7 + 1/2
3x = (-14 + 1)/2
3x = -13/2
x = -13/6
F. 3x + 2 = 2x + 13/3
3x - 2x = 13/3 - 2
x = (13 - 6)/3
x = 7/3
Hope This Helps You!
Answer:
funny I have this question and I thought it was D
Your answer would be C (8,15,17) and E (15,20,15) or is it 25?
Step-by-step explanation:
:)
Answer:
692914.56
Step-by-step explanation:
(9.2 x 102)
= 938.4
(7.1 x 104)
= 738.4
938.4 x 738.4
=
692914.56